2005
DOI: 10.1073/pnas.0507704102
|View full text |Cite
|
Sign up to set email alerts
|

The spread of attention across modalities and space in a multisensory object

Abstract: Attending to a stimulus is known to enhance the neural responses to that stimulus. Recent experiments on visual attention have shown that this modulation can have object-based characteristics, such that, when certain parts of a visual object are attended, other parts automatically also receive enhanced processing. Here, we investigated whether visual attention can modulate neural responses to other components of a multisensory object defined by synchronous, but spatially disparate, auditory and visual stimuli.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
255
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(299 citation statements)
references
References 42 publications
(42 reference statements)
39
255
5
Order By: Relevance
“…A second possibility is suggested by neuroanatomical and neurophysiological studies, which have revealed that the striate cortex receives neuronal projections from auditory cortices, which may facilitate multimodal integration (Clavagnier et al, 2004;Falchier et al, 2002;Rockland and Ojima, 2003;Schroeder and Foxe, 2005). We speculate that these anatomically early connections might allow attentional modulations of sensory activity in one modality to "spread" to sensory cortices in a second modality under certain conditions (Busse et al, 2005). Additional studies are clearly needed to determine the precise nature of the cross-modal attentional effects that we have observed here.…”
Section: Discussionmentioning
confidence: 85%
“…A second possibility is suggested by neuroanatomical and neurophysiological studies, which have revealed that the striate cortex receives neuronal projections from auditory cortices, which may facilitate multimodal integration (Clavagnier et al, 2004;Falchier et al, 2002;Rockland and Ojima, 2003;Schroeder and Foxe, 2005). We speculate that these anatomically early connections might allow attentional modulations of sensory activity in one modality to "spread" to sensory cortices in a second modality under certain conditions (Busse et al, 2005). Additional studies are clearly needed to determine the precise nature of the cross-modal attentional effects that we have observed here.…”
Section: Discussionmentioning
confidence: 85%
“…For example, a visual stimulus can enhance attention to an auditory stimulus localized to the same region of space (31). Interactions between sensory modalities can occur either due to connections between primary sensory regions or through multisensory convergence zones, and can result in competitive, additive, or superadditive effects of sensory stimulation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Most work on attention and objects is in the visual literature [2,21], but similar principles govern auditory perception [22,23,24]. Evidence suggests that attention acts on auditory objects, much as it enhances visual objects [25,26,27].…”
Section: Object-based Attentionmentioning
confidence: 99%